FOREIGN LANGUAGE LEARNING USING A COMMUNICATIVE APPROACH WITH NEW LITERACY THEORY - M. Kholis Amrullah; Husnul Fatimah; Hayatul Mursyida; M. Miftah Arief; Manna Dey (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This study discusses a number of influences related to teachers' understanding of the application of new literature theory and communicative learning, such as teacher trust, teacher education, and teacher professional development. The research is literature-based, with documentary data collection and analysis methods using content analysis. This research focuses on important issues that can help in the development of foreign language teaching curriculum. The focus of discussion in this article includes the lack of understanding of new literacy theories and communicative language teaching methods, curriculum understanding, teacher professional development through new literacy theories, and ideological tensions arising from the foreign language teaching gap in Indonesia. Implementation of the contemporary curriculum may differ between cities and villages. The lack of language activities, especially listening and speaking skills, in the old curriculum is what causes apathy and boredom among students and prevents them from interacting with their communities.